Fatôres de produção de leite em dez municípios mineiros - Martins Fagundes, Lourival (Revista Ceres, 2025)
Milk is a product of economic importance to Brazil and especially to Minas Gerais. Its importance is indicated by the large number of farms dedicated to thiskind of exploitation and by its contribution to the agricultural income of the State.